Zero Water Exchange an Effective Tool for Ecological Balance in Aquaculture Systems (International Journal of Scientific Research in Science and Technology, 2025)
In the present study the fish caught from natural resources is getting depleted every year mainly due to aquatic pollution and over exploitation of the resources. Exploitation is not only of adult stages but also of early stages of life cycle. Hence, the aquatic life and environment is threatened up to an extent that the number of dead points/zones (Non availability of dissolved oxygen (DO) are increasing in the aquatic systems of world over at an alarming rate. In the last four decades, aquaculture developed at a very fast pace due to high demand in the international market coupled with increasing human population. This development could not last longer as the amplitude of the range of development was ecologically imbalance which resulted in the disease outbreak the world over. To get rid of these problems, the ecologically balanced zero water exchange system came into existence and it is now fully scientifically and technically proven technology for its application in enhanced aqua-production systems.